HEAVY METALS CONTENT (Ba, La, Ce) IN THE SOILS OF CHEREPOVETS TECHNOGEACHEMICAL ANOMALY - Yu. Vodianitsky; A. Savichev; O. Rogova (Бюллетень Почвенного института им. В.В. Докучаева, 2010)
With the help of X-ray radiometric method modified for diagnostics of superheavy metals Ba, La, Ce, their content in soils of Cherepovets geochemical anomaly is studied. Values Ultra-heavy metal technogeneities reach their maximum nearness of the Severstal mill. This is especially true for La and Ce, the share of whose technogenicity reaches up to 30-43%. This reflects the accumulative nature of the profile distribution of La and Ce, while in the background areas in humidal landscapes the distribution is eluvial.